Innovating to improve primary care in less developed countries: towards a global model. Issue 4 (23rd July 2015) - Fairall, Lara; Bateman, Eric; Cornick, Ruth; Faris, Gill; Timmerman, Venessa; Folb, Naomi; Bachmann, Max; Zwarenstein, Merrick; Smith, Richard
Abstract : One of the biggest problems in global health is the lack of well trained and supported health workers in less developed settings. In many rural areas there are no physicians, and it is important to find ways to support and empower nurses and other health workers. The Knowledge Translation Unit of the University of Cape Town Lung Institute has spent 14 years developing a series of innovative packages to support and empower nurses and other health workers. PACK (Practical Approach to Care Kit) Adult comprises policy-based and evidence-informed guidelines; onsite, team and case-based training; non-physician prescribing; and a cascade system of scaling up. A series of randomised trials has shown the effectiveness of the packages, and methods are now being developed to respond cost-effectively and sustainably to global demand for implementing PACK Adult. Global health would probably benefit from less time and money spent developing new innovations and more spent on finding ways to spread those we already have.